2014
DOI: 10.1089/cyber.2014.0169
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use and Internet Searches for Medical Information: The Role of Health Anxiety

Abstract: Individuals frequently use the Internet to search for medical information. For some individuals, repeated searches for medical information on the Internet exacerbate health anxiety. Researchers have termed this phenomenon "cyberchondria" and have suggested that cyberchondria might relate to the excessive use of the Internet for other purposes as well. The present study examined associations among Internet searches for medical information, health anxiety, and problematic Internet use (PIU) using a large sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 23 publications
8
89
0
4
Order By: Relevance
“…These findings were consistent with the studies by Fergus and Dolan,[31] Eastin and Guinsler,[16] Baumgartner and Hartmann,[18] Tanis et al .,[21] Lagoe and Atkin,[10] te Poel et al .,[15] Muse et al .,[20] Singh and Brown,[19] White and Horvitz,[32] Singh and Brown,[13] Kim and Lee,[33] Fink et al .,[34] Hadjistavropoulos et al .,[36] and Doherty-Torstrick et al . [35] who found that the higher the health anxiety level among people, the more the need to seek health information and the level of the search for this information.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings were consistent with the studies by Fergus and Dolan,[31] Eastin and Guinsler,[16] Baumgartner and Hartmann,[18] Tanis et al .,[21] Lagoe and Atkin,[10] te Poel et al .,[15] Muse et al .,[20] Singh and Brown,[19] White and Horvitz,[32] Singh and Brown,[13] Kim and Lee,[33] Fink et al .,[34] Hadjistavropoulos et al .,[36] and Doherty-Torstrick et al . [35] who found that the higher the health anxiety level among people, the more the need to seek health information and the level of the search for this information.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study were consistent with the studies by Fergus and Dolan,[31] Eastin and Guinsler,[16] Baumgartner and Hartmann,[18] Tanis et al,[21] te Poel et al .,[15] Singh and Brown,[19] White and Horvitz,[32] Kim and Lee,[33] Fink et al .,[34] and Doherty-Torstrick et al . [35] on the direct relationship between health anxiety and the need for health information, the frequency and rate of health information seeking, and the use of primary care.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, these studies have shown that anxiety sensitivity, health anxiety and problematic internet use are risk factors for ciberchondria (Fergus & Dolan, 2014;Fergus & Spada, 2017). It has also been shown that ciberchondria potential overlaps with obsessive compulsive symptoms (Fergus & Russell, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Despite the potential promise for understanding cyberchondria through the lens of PIU, to date, only indirect data link these two constructs. More precisely, Fergus and Dolan () found greater PIU among individuals who reported experiencing increased health anxiety following Internet searches for health‐related information relative to respondents who reported either no change or a decrease in health anxiety following those searches. The purpose of this two‐part study was to provide the first known direct examination of an association between cyberchondria and PIU in Study 1.…”
Section: Introductionmentioning
confidence: 99%